Implementation of Serverless Architecture and Real-Time Database on Laprak Tracker Application using ReactJS and Firebase - Al-mutawalli, Haidar; Daulay, M. Raghif Hibrizi; Khairi, Muhammad Imam; Lubis, Habiburrozzaq; Ramadan, Bayu Azi; Furqan, Mhd (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2026)
Management of laboratory practicum reports often faces challenges such as inefficient progress tracking and manual data synchronization between students and laboratory assistants. This research aims to develop a web-based application named "Laprak Tracker" to streamline this process. The system is built using a serverless architecture with Google Firebase as the backend and Cloud Firestore for real-time data synchronization. The frontend is developed using ReactJS with a Single Page Application (SPA) approach to ensure responsiveness and high performance. The methodology used is the Waterfall model, encompassing requirements analysis, system design, implementation, and testing. Testing results using the Black Box method show that all features, including authentication, module management, and real-time status updates (ACC tracking), function correctly. This application provides an efficient solution for students to monitor their practicum progress and ensures data integrity through a centralized cloud system.